Naturalistic Intelligence and Problem-Solving Skills: Study of Its Connectivity Through Environmental Photovoice Projects - Ekanara, Bambang; Ramdana, Ahmad; Leksono, Suroso Mukti; Isfiani, Ilma Riksa; Safkolam, Roswanna (Universitas Sultan Ageng Tirtayasa, 2023)
Sensitivity to environmental concepts is closely related to naturalistic intelligence, as well as concern for finding solutions to environmental problems through problem-solving skills. This study aimed to determine the correlation between naturalistic intelligence and problem-solving ability through environmental photovoice project. Correlational research method was used in this study with purposive sampling technique. Population were 10th grade students of senior high school with specific science class as a sample. Naturalistic intelligence was measured by using naturalistic questionnaire. The problem-solving ability indicates in photovoice project and measured by using a photovoice assessment rubric developed based on problem-solving indicators. The results showed that the average of students’ naturalistic intelligence was 75.82 in score, it’s mean that students’ naturalistic intelligence belong to high criteria. The average of students’ problem-solving skills was 66.12 in score belong to high criteria as well. The result of this research shows the value of correlational coefficient was 0.582. This means that there was strong positive relationship between naturalistic intelligence and the problem-solving skills through photovoice project on the environmental topic. These findings indicate that naturalistic intelligence are closely related to problem-solving skills. Finally, we discuss the relationship of naturalistic intelligence and problem-solving skills and provide suggestions for further work.